The public environmental policy in Libya (Journal of human and social sciences, 2023)
Public policies in Libya were affected by internal and external variables after the events of the February 17, 2011 revolution. As the lives of citizens in various political, economic, social and environmental fields were affected by these variables. This study represents an attempt to evaluate the environmental policy after the events of 2011, as it aims to know the most important internal determinants that affected the environmental policy in Libya negatively or positively, as well as the opportunities and challenges in the external determinants affecting the environmental public policy in Libya. The study also aims to know the legislative and institutional frameworks that govern the process of making, implementing and evaluating environmental public policy in Libya.
Keywords: Environmental Policy; Public Policy Evaluation; Internal and External Determinants; Legislative and Institutional Frameworks